(untitled) (Proceedings of the World Disability & Rehabilitation Conference, 2019)
People with disabilities (PWDs) account for about 15% of the world population, and they need to be provided with opportunities for comfortable living. There are reported models to categorise PWDs, but none support to identify their capabilities and limitations. This has limited their employability with their residual capabilities depriving them of an independent life. Literature suggests a multi-dimensional model to enable them to be employed. Thus, the aim of this research was to categorise people with physical disabilities (PPDs) based on their capabilities for performing work activities in industry. First, typical manual work-tasks in industry were identified from work activities prescribed in Pre-determined Motion Time Systems (PMTS). Then, Ranges of Motion (ROM) associated with each of the body regions were captured and refined using a walkthrough and interview approach with Consultant Orthopaedic Surgeons (n = 6) and Prothetists and Orthotists (n = 3). Body regions and joints both in the upper and lower extremities required for performing work activities in industry were identified. Finally, ROM required for performing PMTS activities were mapped by selecting a sample of PPDs (n = 92). This categorisation is expected to be used by potential employers to recruit PPDs based on their residual capabilities to perform work-tasks, identify training needs of PPDs and to decide on assistive devices and special facilities to help them independently carry out work activities. Further research is needed to use the categorisation in an industrial setting to evaluate its feasibility as a tool to help recruitment of PPDs.